2007
DOI: 10.1039/b606047c
|View full text |Cite
|
Sign up to set email alerts
|

Engineering void space in organic van der Waals crystals: calixarenes lead the way

Abstract: Seemingly non-porous organic solids have the ability for guest transport and have also been shown to absorb gases, including hydrogen, methane and acetylene, to varied extents. These materials also show potential for gas separation technology, display remarkable water transport through hydrophobic crystals, and clearly show that molecules within crystals are capable of cooperating with guests as they move through non-porous environments. This work is presented within a broader topic which also encompasses crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
213
0
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 455 publications
(220 citation statements)
references
References 30 publications
4
213
0
3
Order By: Relevance
“…The tunable nature of the container cavity serves to trap desired molecular shapes and functionalities with typically high selectivity. [19] The burgeoning interest in host-guest materials has given rise to exceptionally complex single- [20] and multicomponent [21] self-assembled structures, and such materials have been incorporated into sensors based on fluorescence, [22] surface acoustic wave (SAW), [23] and quartz crystal microbalance (QCM) [24] and polymer-coated chemiresistors. [25] In this article, we report the use of ultra-thin films of container molecules as sensory layers on an existing OTFT, resulting in both enhanced sensitivity as well as shape discrimination between vapors of small-molecule analytes.…”
mentioning
confidence: 99%
“…The tunable nature of the container cavity serves to trap desired molecular shapes and functionalities with typically high selectivity. [19] The burgeoning interest in host-guest materials has given rise to exceptionally complex single- [20] and multicomponent [21] self-assembled structures, and such materials have been incorporated into sensors based on fluorescence, [22] surface acoustic wave (SAW), [23] and quartz crystal microbalance (QCM) [24] and polymer-coated chemiresistors. [25] In this article, we report the use of ultra-thin films of container molecules as sensory layers on an existing OTFT, resulting in both enhanced sensitivity as well as shape discrimination between vapors of small-molecule analytes.…”
mentioning
confidence: 99%
“…1 Recent examples indicate that a permanent pore or channel is not necessarily a requirement for the absorption of gases. 2 Dynamic structural changes in coordination polymers induced new channels into which guest molecules were incorporated. 3 Atwood et al recently demonstrated that non-porous organic solids could expand by gas induced transformations.…”
mentioning
confidence: 99%
“…It should be pointed out that the chemistry of dimeric capsules is better known than that of capsules of higher multiplicities, this fact having its reflection in number of reports that have appeared. [67][68][69][70] The above review, albeit presenting only chosen examples of trimeric and hexameric capsules highlights to some extent their formation and properties which are promising for their applications.…”
Section: Methodsmentioning
confidence: 99%